2020
DOI: 10.1039/d0nr02788j
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona fingerprinting to differentiate sepsis from non-infectious systemic inflammation

Abstract: Exploitation of the nanoparticle protein corona to identify proteomic fingerprints in blood that differentiate non-bacterial systemic inflammation from sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 71 publications
1
63
0
Order By: Relevance
“…Our group has previously detected histone proteins in human and mouse liposomal corona, both ex vivo and in vivo. 9,11,12 Moreover, human histone proteins (H2B and H4) have also been found to interact with colloidal gold NPs upon incubation with human plasma. 54 Finally, De Paoli and colleagues demonstrated that calf thymus histone H1 can bind onto carboxylated-multiwalled carbon nanotubes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group has previously detected histone proteins in human and mouse liposomal corona, both ex vivo and in vivo. 9,11,12 Moreover, human histone proteins (H2B and H4) have also been found to interact with colloidal gold NPs upon incubation with human plasma. 54 Finally, De Paoli and colleagues demonstrated that calf thymus histone H1 can bind onto carboxylated-multiwalled carbon nanotubes.…”
Section: Discussionmentioning
confidence: 99%
“…PEGylated liposomes were found to reproducibly interact with low molecular weight (MW) plasma proteins of low abundance. [9][10][11][12]15 In order to assess the potential interaction of cfDNA with PEGylated liposomal surfaces, plasma-incubated liposomes were purified by size exclusion chromatography (SEC), shown in Fig. 1A, as described previously.…”
Section: Plasma Incubation and Biomolecule Corona Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have identified this concept for several life-threatening diseases such as cancers and neurodegenerative diseases. 16 , 60 , 95 101 …”
Section: Proteomics Technologies Enable Biomarker Discovery: Implicatmentioning
confidence: 99%